Luis Artigue, Tres, dos, uno... jazz, Valladolid, Fundación Jorge Guillén, 2007, 74 pp. - Martínez Fernández, José Enrique (Estudios Humanísticos. Filología, 2008)
Luis Artigue, Tres, dos, uno... jazz, Valladolid, Fundación Jorge Guillén, 2007, 74 pp.